1998
DOI: 10.1055/s-2007-1006901
|View full text |Cite
|
Sign up to set email alerts
|

Free Groin Flap for Reconstruction of the Tongue and Oral Floor

Abstract: The authors report the use of free groin flaps to close intraoral defects in 24 patients following ablative tongue cancer surgery. The lateral thin portion of the flap was used for tongue reconstruction, and the deepithelialized medial thick portion for filling the mandibular defect and for covering the important vessels in the neck. In lean patients, if the medial deepithelialized portion was too thin for adequate coverage, the proximal sartorius muscle was included to prevent postoperative orocervical fistul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The statistical heterogeneity was high at I 2 = 70%. Meta-analysis of 1331 patients from 28 evaluable studies 8,9,20,23,28,30,33-36,38-40,42,47,48,50,53-55,57,58,61,64,74,85 showed a pooled risk of OCF of 8.55% (95% CI, 5.71%-11.4%, I 2 = 71.8%) among patients undergoing free flap reconstruction (Figure 3A), compared to 8.02% (95% CI, 5.27%-10.8%, I 2 = 72.7%) among 1449 patients undergoing regional flap reconstruction from 34 evaluable studies 10,13,14,16,19,21,24-26,32,41,44,45,51,56,59,60,62,63,65-67,69,71,73,75,76,78,80,82-84 (Figure 3B). Pooled risk of fistula was 6.74% (95% CI, 4.50%-8.97%, I 2 = 38.6) among 1133 patients undergoing segm...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical heterogeneity was high at I 2 = 70%. Meta-analysis of 1331 patients from 28 evaluable studies 8,9,20,23,28,30,33-36,38-40,42,47,48,50,53-55,57,58,61,64,74,85 showed a pooled risk of OCF of 8.55% (95% CI, 5.71%-11.4%, I 2 = 71.8%) among patients undergoing free flap reconstruction (Figure 3A), compared to 8.02% (95% CI, 5.27%-10.8%, I 2 = 72.7%) among 1449 patients undergoing regional flap reconstruction from 34 evaluable studies 10,13,14,16,19,21,24-26,32,41,44,45,51,56,59,60,62,63,65-67,69,71,73,75,76,78,80,82-84 (Figure 3B). Pooled risk of fistula was 6.74% (95% CI, 4.50%-8.97%, I 2 = 38.6) among 1133 patients undergoing segm...…”
Section: Resultsmentioning
confidence: 99%
“…Pooled risk of fistula was 6.74% (95% CI, 4.50%-8.97%, I 2 = 38.6) among 1133 patients undergoing segmental mandibulectomy in 21 studies, 13,16,20,22,23,28,33,35,39,40,42,47,48,50,51,53,54,57,69,75,77 compared to 5.48% (95% CI, 2.41%-8.45%, I 2 = 54.6%) among 556 patients without segmental mandibulectomy in 24 studies. 10,12,30,31,34,38,41,[43][44][45]52,[54][55][56]59,65,67,68,71,73,74,78,80,82 A total of 591 patients from 12 studies 9,17,18,20,23,…”
Section: Meta-analysismentioning
confidence: 99%
“…Fistulas or salivary leaks complicate postoperative management and have been reported in up to 30% of oral cavity resections requiring free flap reconstruction. 27,28 A metaanalysis by Tassone et al 29 reported a pooled prevalence of fistula in 8.6% of oral cavity resections reconstructed with free tissue. Several series have compared rates of complications between OCRFFFs and FFFs, and generally no differ-ence has been seen; however, complication rates may have been somewhat affected by studies that were inadequately powered to detect differences on the magnitude of 5% to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…15 The classic free groin flap has also been used to minimize donor-site morbidity in head and neck reconstruction. 16 Although several reconstructive methods and flaps have been developed since the 1970s, several important points should be kept in mind, such as minimizing early postoperative complications that may prolong hospitalization and become life-threatening, maintaining postoperative functions, and decreasing the degrees of surgical invasiveness and donor-site morbidity. To shorten operative time, the preferred flap is one that can be elevated simultaneously with tumor resection while the patient remains in the supine position.…”
Section: History Of Reconstructive Methods After Glossectomymentioning
confidence: 99%